2008
DOI: 10.1017/s1461145708009371
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the endocannabinoid system in phencyclidine-induced cognitive deficits modelling schizophrenia

Abstract: Recent advances in the neurobiology of cannabinoids have renewed interest in the association between cannabis and schizophrenia. Our studies showed that chronic-intermittent phencyclidine (PCP) treatment of rats, an animal model of schizophrenia-like cognitive deficit, impaired recognition memory in the novel object recognition (NOR) test and induced alterations in CB1 receptor functionality and in endocannabinoid levels mainly in the prefrontal cortex. In this region, we observed a significant reduction in GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 107 publications
(94 reference statements)
3
59
0
2
Order By: Relevance
“…As successful antipsychotic therapy reversed the increased levels of AEA (186, 472), this increase might represent an adaptive reaction to overactivation of dopamine D2 receptors (472). In rats, it was suggested that AEA and 2-AG play a potentially different role (protective and counterprotective, respectively) in the schizophrenialike cognitive and negative symptoms induced by chronic phencyclidine, and that cannabis use or CB1 antagonism and FAAH inhibition might exacerbate or improve, respectively, such symptoms by modifying endocannabinoid signaling (5,313,883).…”
Section: Schizophreniamentioning
confidence: 99%
“…As successful antipsychotic therapy reversed the increased levels of AEA (186, 472), this increase might represent an adaptive reaction to overactivation of dopamine D2 receptors (472). In rats, it was suggested that AEA and 2-AG play a potentially different role (protective and counterprotective, respectively) in the schizophrenialike cognitive and negative symptoms induced by chronic phencyclidine, and that cannabis use or CB1 antagonism and FAAH inhibition might exacerbate or improve, respectively, such symptoms by modifying endocannabinoid signaling (5,313,883).…”
Section: Schizophreniamentioning
confidence: 99%
“…By contrast, rodents do not provide a good model for assessing detrimental effects on LTM. Nevertheless, to date, almost all NOR tests have been done in rodents and this test is increasingly used in rodent animal models of various diseases including Alzheimer's Disease (Donkin et al, 2010;Greco et al, 2010;Hillen et al, 2010;Lu et al, 2009;Mouri et al, 2007;Nishida et al, 2006;Taglialatela et al, 2009), schizophrenia (Hauser et al, 2009;McLean et al, 2009;Neill et al, 2010;Ozawa et al, 2006;Powell et al, 2007;Vigano et al, 2009), and Down's syndrome (Lockrow et al, 2010). The absence of any external reinforcement in the NOR test is particularly important as it makes it more comparable to memory tests in human, which are normally conducted without the use of positive or negative reinforcers such as food and electric shock (Ennaceur and Delacour, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent exposure to synthetic or natural cannabinoid agonists has been reported to induce impairments in object recognition memory at adulthood in both male and female rats and in spatial working memory without affect other forms of memory (aversive memory or spatial learning) 13,14 . Moreover adolescent exposure to THC worsened the cognitive impairment induced by intermittent chronic administration of phencyclidine, an animal model of schizophrenia-like cognitive deficit 15 . In contrast the co-treatment with the CB1 receptor antagonist AM251 recovered it 16 .…”
Section: Animal Studiesmentioning
confidence: 99%
“…Interestingly, when an animal model used to induce schizophrenia-like symptoms was used during the periadolescent period, a decrease in CB1 receptor expression and/or G protein coupling has been observed in cerebral areas relevant to schizophrenia. Reciprocal increase in FAAH and decrease CB1 receptor expression was present in the caudate putamen of socially isolated rats 19 , an environmental model of schizophrenia and a specific increase in 2-AG levels was measured in the PFC of rats chronically treated with phencyclidine (PCP), associated with reduced functionality of the CB1 receptor in this brain area 15 . In line with this, in the hippocampus of maternally deprived rats a decrease in CB1 receptor expression and an increase in 2-AG levels have been observed.…”
Section: Animal Studiesmentioning
confidence: 99%